Computer technology: potential use for music education (Pedagogy of Higher and Secondary Education, 2012)
Varnavskaya L. Computer technology: potential use for music education.The actuality of the material, given in the paper, is caused by the rapid development of computer technologies, their widespread application in science, education and everyday life. The necessities of using the means of computer technologies in the modern informative world, in musical education to be exact, attract the attention of music teachers and require the scientific approach to this problem. Some of the computer technologies applications in music classes, viewed in the paper, define their wide potential in the process of teaching music.
Keywords: computer technologies; educational process; musical education